Potensi Perampasan Wilayah Masyarakat Hukum Adat dalam Undang-undang Nomor 11 Tahun 2020 tentang Cipta Kerja - Sari, Ria Maya (Jurnal Mulawarman Law Review, 2021)
The Indonesian government seeks to boost the Indonesian economy by facilitating foreign investment in Indonesia, which is realized through the enactment of the Omnibus Law on Job Creation Number 11/2020 and the Revision of the Mineral and Coal Mining Law Number 3/2020, both of which aim to legitimate investment in Indonesia in terms of natural resource management and to improve the welfare of the Indonesian people through the creation of jobs from these investments. However, those two legislations also pose several potential threats to indigenous peoples in the form of expropriation of their customary territories. This is further worsened by the absence of a special act on the fulfillment, recognition and protection of indigenous peoples and their rights, which lead to exacerbate the structural agrarian conflicts between the government, corporations/investors and indigenous peoples that would further impose expensive conflict resolution costs and threaten the investment itself. The urgency of the enactment of the Indigenous Peoples Bill is an absolute necessity to provide legal certainty for the protection of indigenous peoples in the midst of high investment aggression, as well as to the investors themselves.